The geometrical and kinematical analysis of the flow of polymer through the screw-based plasticating system - Sikora, R.; Sasimowski, E. (Polimery, 2022)
Earlier investigations [1-4] on the lengthwise flow and the transverse flow of polymer particles through the helical channel in the screw-based plasticating system are continued to study the resultant flow in the models examined, i.e., one involving the rotating barrel and the other involving the rotating screw. The trajectories followed by polymer particles in the two models were found to be different. In the rotating barrel model, the spiral lead of the polymer particle trajectory was found to be higher (Figs. 6, 7) than that in the rotating screw model (Figs. 8, 9), because the peripheral speeds of the barrel and the screw are different. The spiral motion pathway is laevorotatory in the former and dextrorotatory in the latter model. In the vicinity of the helical channel wall (direction of motion varies by pi/2), polymer particles behave identically in either model.